Exploration and evaluation of the tools used to identify first year at-risk students in health science courses: A systematic review. Issue 4 (December 2019) - Goradia, Tirtha; Bugarcic, Andrea
Abstract: Objectives: High attrition rate in first year health science courses including allied health is a common problem in the higher education sector. This systematic review aims to explore the tools used by educators in identifying first year, at-risk students studying health science courses within higher education. The review identifies the tools and investigates their effectiveness in identifying at-risk students. Methods: A mixed-methods systematic review of original research was undertaken exploring the tools used or developed for identification of the at-risk health science students in their first year of study. Following databases were searched: Academic OneFile, CINAHL PLUS, ERIC, ScienceDirect and Google Scholar. Results: Collectively, the included studies (n = 13) revealed that a combination of both academic and non-academic factors are most effective in identifying at-risk students. All 13 identified studies developed tools based on one or more of the following three categories: those examining the personal background, academic preparedness and the student perceptions of their own abilities and readiness. Conclusion: With students enrolling into health science courses coming from various diverse academic and personal backgrounds, the tools identified in this systematic review could enhance early identification of at-risk students, thereby enabling educational institutions to take timely educational interventions to support them.